Association between Myeloperoxidase and High Sensitive Troponin I on Myocardial Contractility in Acute Myocardial Infarction Patients - Wasyanto, Trisulo; Meilus, Budi Patria; Yasa, Ahmad (Indonesian Journal of Medicine, 2020)
Background: Myeloperoxidase (MPO) levels have been shown to have prognostic values for death events in acute myocardial infarction (AMI) patients. Increased levels of high sensitive troponin I (hs Trop I) are associated with poorer prognosis in AMI patients. This study aimed to determine the association between levels of MPO and hs troponin I at admisson on myocardial contractility in AMI patients.Subjects and Method: This was a prospective observational analytic study, conducted at Dr. Moewardi General Hospital, Surakarta, from November1, 2018 to January 31, 2019. The study subjects were patients who were diagnosed with AMI. A total of 23 patients were included in this study; 15 patients with ST elevation myocardial infarction (STEMI) and 8 with non ST elevation myocardial infarction (NSTEMI). The dependent variable was myocardial contractility. The independent variables were MPO and hs Trop I. Blood tests for MPO and hs Trop I was measured at admission and the left ventricular ejection fraction (LVEF) was measured when predischarge by the Simpson method to examine myocardial contractility. The data were analyzed by Pearson correlation run on SPSS 22.  Results: hs Trop I (r= -0.53; p= 0.009) and MPO (r= -0.15; p=0.487) decreased LVEF.Conclusion: Hs Trop I at admission has a correlation with myocardial contractility, and no correlation of MPO at admission with myocardial contractility in AMI patients.Keywords: Myeloperoxidase, High sensitive Troponin I, Acute myocardial infarctionCorrespondence: Trisulo Wasyanto. Department of Cardiology and Vascular Medicine, Faculty of Medicine, Universitas Sebelas Maret/ Dr. Moewardi Hospital. Jl. Kol. Sutarto 132, Surakarta 57126, Central Java, Indonesia. Email: trisulo.wasyanto@gmail.com.Indonesian Journal of Medicine (2020), 05(04): 265-271https://doi.org/10.26911/theijmed.2020.05.04.01.